Birds and animals in the Dvarashakha of Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
Birds and animals in the dvarashakha (vertical branches of the entrances) of garbhagriha (sanctum sanctorum) of the Sitaleshwar Temple.